Characterization and comparison of complete mitogenomes of three parrot species (Psittaciformes: Psittacidae) - Hongyi Liu; Yiting Yang; Nan Xu; Rong Chen; Zhaoshui Fu; Silin Huang (Mitochondrial DNA. Part B. Resources, 2019)
In this paper, we characterized the complete mitogenomes of Aratinga solstitialis, Pionites leucogaster, and Poicephalus senegalus through Sanger sequencing method. The full lengths of the three mitogenomes are 16,986 bp, 18,858 bp, and 18,022 bp, respectively. All genes exhibit original gene arrangement in A. solstitialis mitogenome, but gene rearrangements occur in P. leucogaster and P. senegalus mitogenomes. Bayesian tree indicated that the three parrots were not closely related to each other. The results obtained here can contribute to phylogenetic analysis and biological conservation of parrots further.